Role of Nutraceuticals in Hypolipidemic Therapy - Barbagallo, Carlo M.; Cefalù, Angelo Baldassare; Noto, Davide; Averna, Maurizio R. (Frontiers in Cardiovascular Medicine, 2015)
Nutraceuticals are food components or active ingredients present in foods and used in therapy. This article analyzes the characteristics of the molecules with a lipid-lowering effect. The different nutraceuticals may have different mechanisms of action: inhibition of cholesterol synthesis primarily through action on the enzyme HMG-CoA reductase (policosanol, polyphenols, garlic and, above all, red yeast rice), increase in LDL receptor activity (berberine), reduction of intestinal cholesterol absorption (garlic, plant sterols, probiotics), and also the ability to interfere with bile metabolism (probiotics, guggul). Based on the different mechanisms of action, some nutraceuticals are then able to enhance the action of statins. Nutraceuticals are often used without relevant evidence: mechanisms of action are not clearly confirmed; most of clinical data are derived from small, uncontrolled studies, and finally, except for fermented red rice, there are no clinical trials which may document the relationship between these interventions and the reduction of clinical events. Therefore, among all nutraceuticals, it is necessary to extrapolate those having a really documentable efficacy. However, these kinds of treatments are usually well-tolerated by patients. Overall, subjects with a middle or low cardiovascular risk are the best indication of nutraceuticals, but they may also be useful for patients experiencing side effects during classical therapies. Finally, in consideration of the additive effect of some nutraceuticals, a combination therapy with classical drugs may improve the achievement of clinical targets. Thus, nutraceuticals may be a helpful alternative in hypolipidemic treatment and, if properly used, might represent a valid strategy of cardiovascular prevention.